Stem-branch and stem-root formation for sculpture - Oko-Martey, Frederick Martey (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Fine Arts in Sculpture.